Novel compounding and the emergence of structure in two young sign languages. Issue 1 (19th December 2018) - Tkachman, Oksana; Meir, Irit
Abstract : This paper investigates how structure emerges in a young language, focusing on compounding in two young sign languages, Israeli Sign Language (ISL) and Al-Sayyid Bedouin Sign Language (ABSL). We focus on novel compounds (tokens invented on the spot) to ensure that we are studying a productive process and to avoid issues contingent with lexicalization. We found that both languages make use both of compounding and size-and-shape classifier constructions (SASS-constructions), but ISL and ABSL have conventionalized different structures and the structures they do use are conventionalized to different degrees. We discuss the similarities and differences of those constructions in ISL and ABSL in the context of structure emergence and language evolution.